The effect of water shower spray on stress physiology and mortality in broiler chickens subjected to road transportation under the hot and humid tropical condition - Zainool Abidin, Zulaikha; Sulaiman, Nur Farrah Aizurin; Ramiah, Suriya Kumari; Awad, Elmutaz Atta; Idrus, Zulkifli (Springer, 2022)
This study was performed to investigate the effect of water shower spray on rectal temperature (RT), serum levels of corticosterone (CORT), heat shock protein (HSP) 70 and creatine kinase (CK) in broiler chickens road transported at different times of the day. A total of 320 male broiler chickens (35 days of age) were crated and subjected to either water shower spray (WS) for 10 minutes or no water shower (control). The WS and control broilers were then loaded into an open truck and transported either from 0900 h to 1100 h (29.0oC and 89.0% RH) (AM) or 1900 h to 2100 h (26.0oC and 94.0% RH) (PM) with an average speed of 80 km/h. The CORT of AM birds were significantly reduced by WS, but the treatment had negligible influence on the PM group. Transportation during AM significantly elevated RT, CORT and HSP70 compared to the PM group. Water shower spraying of birds before transit significantly reduced RT and HSP70 compared to controls. Neither water shower treatment nor transportation time had a significant on CK and mortality rate of broilers. In conclusion, water shower spray is beneficial to alleviate the physiological stress response in road transported broilers under the hot and humid tropical environment.